2020
DOI: 10.47405/mjssh.v5i10.517
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges in Teacher Leadership

Abstract: Teacher leadership significantly promotes development and efficiency at schools. However, the practice of teacher leadership is slammed with challenges that impact its progression and effective implementation in schools. Therefore, the present study focused on the key terms, problems, and obstacles of teacher leadership based on domestic and international works of literature on teacher leadership practices. The study discussed the notion of teacher leadership before it addressed the challenges in the practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Based on issues related to principals, it was found that there are principals who have little confidence in the role of teachers as teacher leaders (Kamaruzaman et al, 2020; Monjong and Fon, 2016; Ross et al, 2011). This situation may stem from the multiple and ambiguous issues related to the definitions of the concept of leadership (Cheung et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on issues related to principals, it was found that there are principals who have little confidence in the role of teachers as teacher leaders (Kamaruzaman et al, 2020; Monjong and Fon, 2016; Ross et al, 2011). This situation may stem from the multiple and ambiguous issues related to the definitions of the concept of leadership (Cheung et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, those school leaders who create a school culture that does not encourage teacher leadership have made teacher leadership difficult to implement (Durias, 2010; Flood and Angelle, 2017). The lack of a culture that supports the implementation of teacher leadership will definitely lead to teachers being reluctant or refusing to become teacher leaders (Abdul Shukor, 2012; Kamaruzaman et al, 2020). This is because some teachers and staff in the school have been accustomed to a concept of leadership that is attached to formal positions, which led to teachers who do not hold formal positions being less accepted as leaders by other teachers (Chew and Andrews, 2010; Friedman, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation